Regional Potential Optimization and Nutrition Awareness Enhancement through SEGANTING Program in Lebosari: Optimalisasi potensi daerah dan peningkatan sadar gizi melalui program SEGANTING di Lebosari - Ahmada Wildan Afifi; Ragil Satria Wicaksana; Andriani Mulyono; Aliefha Amelia; Fatma Kurnia Sari; Anggi Rian Al Miftah; Sella Ayu Pratiwi; Dian Alfianti; Ima Imroatul Aziziah; Rida Tiara Sari; Risma Widiyawati; Wa Ode Ummahatul Muminin; M. Yusril Arif (Universitas Lancang Kuning, 2024)
Stunting or a condition where an individual's height is lower than the majority of their peers due to nutritional issues, poses a significant challenge in the village of Lebosari. The relatively high stunting rates indicate a lack of nutritional awareness and suboptimal utilization of local resources. To address this issue the SEGANTING program has been implemented as a holistic solution. Involving the community in the Discovery, Dream, Design, and Destiny phases, the program includes food innovation, the Community Nutrition Corner, and the village's UMKM bazaar. Prior to the program's commencement, the pre-test results showed an average correct answer rate of 40.33. After the program's implementation, there was a 54% increase, with an average correct answer rate reaching 88.00 in the post-test. This reflects the significant contribution of the SEGANTING program in enhancing the understanding of the Lebosari community regarding nutritional awareness and stunting prevention through the optimization of the village's potential.